Impact of impurity seeding on the electron energy distribution function in the COMPASS divertor region. (2nd November 2020) - Dimitrova, M; Popov, Tsv K; Kovacic, J; Dejarnac, R; Gunn, J P; Ivanova, P; Imrisek, M; Stöckel, J; Vondracek, P; Hron, M; Panek, R; ,
Abstract: In the COMPASS tokamak, series of experiments were performed aimed at studying the impact of nitrogen, neon, and argon impurity seeding on the electron energy distribution function (EEDF) in the divertor region. The experiments were conducted in D-shaped, L-mode, deuterium plasmas. In order to obtain the radial distribution of the floating potential, ion saturation current, electron temperatures, and densities, the current-voltage characteristics were measured by Langmuir probes embedded in the COMPASS tokamak divertor. The properties of the plasma in the divertor region were measured before and during impurity seeding. Before the N2 seeding, the EEDF was bi-Maxwellian with a low-energy electron fraction with temperatures 3.5–5 eV, and a higher-energy one with temperatures in the range of 10 eV to 23 eV. During seeding with an increasing number of molecules per second, the EEDF changed from bi-Maxwellian to Maxwellian and the electron temperature decreased. The time-evolution was studied of the change in the EEDF during N2 seeding. When the seeding was carried out by a valve in the private flux region, the duration of the transition from a bi-Maxwellian to a Maxwellian EEDF was about 10–15 ms. When the N2 seeding took place through a low-field side valve, the transition from a bi-Maxwellian to a Maxwellian EEDF took longer −25–45 ms. The temporal evolution was also analyzed of the plasma parameters' radial profiles when neon and argon were puffed using a valve in the divertor low-field side. The application is discussed of the probe measurements' results to calculating the parallel heat-flux densities in the divertor region of the COMPASS tokamak.